1994
DOI: 10.1071/ea9940835
|View full text |Cite
|
Sign up to set email alerts
|

Petiole sap nitrate is better than total nitrogen in dried leaf for indicating nitrogen status and yield responsiveness of capsicum in subtropical Australia

Abstract: This study was conducted to assess the usefulness of petiole sap nitrate and total nitrogen (N) in dried leaf for determining N status and yield response in capsicum (Capsicum annuum L.) grown with plastic mulch and trickle irrigation in subtropical Australia. Five rates of N (0, 70, 140,210, 280 kg/ha) were applied in factorial combination with 2 rates of potassium (K: 0, 200 kg/ha) in randomised block experiments to capsicum cv. Bell Tower grown at Bundaberg Research Station in spring 1990 and autumn 1991. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 16 publications
1
29
0
2
Order By: Relevance
“…Despite this interaction, the NO3sap5 parameter was affected mainly by fertilization and therefore is a good indicator of relative nitrogen supply. A study of peppers demonstrated that the sap nitrate content of the petiole is a better indicator of plant nitrogen status than the total nitrogen concentration in the blades and petioles of the dried leaves (Olsen and Lyons 1994). In this study, the NO3sap5 measured in broccoli had a wide range (averaging between 1200 and 3500 ppm) in response to fertilizer treatments.…”
Section: Nitrate Content Of the Sapmentioning
confidence: 79%
“…Despite this interaction, the NO3sap5 parameter was affected mainly by fertilization and therefore is a good indicator of relative nitrogen supply. A study of peppers demonstrated that the sap nitrate content of the petiole is a better indicator of plant nitrogen status than the total nitrogen concentration in the blades and petioles of the dried leaves (Olsen and Lyons 1994). In this study, the NO3sap5 measured in broccoli had a wide range (averaging between 1200 and 3500 ppm) in response to fertilizer treatments.…”
Section: Nitrate Content Of the Sapmentioning
confidence: 79%
“…Analysis of NO 3 -concentration in soil solution obtained with ceramic cup suction samplers from the root zone (Hartz et al, 1993;Burt et al, 1995) and in petiole sap Hochmuth, 1994Hochmuth, , 2007Olsen and Lyons, 1994) have been suggested as methods for on-going monitoring of, respectively, the immediately available soil N and crop N status. Recent studies within greenhouse vegetable production systems (Granados et al, , 2007Gallardo et al, 2006) have demonstrated that soil solution nitrate concentration is very sensitive to crop N management.…”
Section: Introductionmentioning
confidence: 99%
“…This result indicates that determining leaf petiole nitrate-N content through the Cardy meter might be a rapid and reliable means to determine potato plant N status in this semi-arid region where either no soil and plant analysis laboratories exist or they are difficult to access. Some research has found that the petiole sap nitrate-N measurement is more sensitive to N fertilizers and a better indicator of plant N status and crop yield than petiole total N measured in dried leaf petioles (Olsen and Lyons 1994).…”
Section: Kellhuiri Vinto Coopani San Juan Circamentioning
confidence: 99%